Peningkatan Kualitas Air Sungai di Desa Padang Batung Hulu Sungai Selatan dengan Memanfaatkan Eceng Gondok sebagai Biofilter Alami: Improving River Water Quality in Padang Batung Village, Hulu Sungai Selatan by Utilizing Water Hyacinth as a Natural Biofilter - Nabil, Sepianur Ahmad; Nurhasanah, Astri; Mulyadi, Paska Apriyani; Husein, Rahmatullah; Sari, Nukhak Nufita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service program was carried out in Padang Batung Village, Hulu Sungai Selatan Regency, South Kalimantan, which is one of the areas affected by water pollution from mining activities. Field observations and information from the local Agricultural Extension Agency (BPP) indicated that the river water tends to be acidic, especially after rainfall that carries mining sediments into the stream. The purpose of this activity was to introduce the use of water hyacinth (Eichhornia crassipes) as a natural biofilter to improve water quality and to enhance community awareness regarding the potential of local weeds. The biofilter experiment was conducted by placing water hyacinth in the river flow confined by nets on both sides. Water pH was monitored weekly for 3 weeks at 3 observation points. Results showed an increase in pH from 4.37–4.43 in the first week to 4.61–6.44 in the second week, followed by stabilization at 5.32–5.46 in the third week. These findings demonstrate water hyacinth's ability to neutralize acidic water through phytoremediation. In addition, community outreach produced positive responses. Farmers who initially considered water hyacinth as a nuisance began to recognize its potential as a simple, low-cost, and environmentally friendly biofilter. This activity successfully increased public knowledge while proving the role of water hyacinth in reducing water pollution in Padang Batung Village.